Legal Protection of Third Parties as Fiduciary Guarantee Holders against Assets Designated as Bankruptcy Boedel by the Curator (Case Study Decision No.2/Pdt.Sus-Other-Lain/2019/PN.Niaga Medan jo. No.7/Pdt.Sus- PKPU/2018/PN.Niaga Medan) - Kartika, Sahnaz; Sunarmi, Sunarmi; Purba, Hasim; Harianto, Dedi (Budapest International Research and Critics University, 2021)
This study is an analytical descriptive study of normative juridical law. Constitutional, conceptual and cases based approach is used for this research. The data comes from secondary data resources. The location of this research is on Medan District Court Class I A, particulary by interviewing commercial judge and the curator. The data collection techniques and tools are library research, field research, document studies and interview. The data qualitatively analyzed.The results of the study indicate that the third party’s lawsuit against the property that is designated as boedel bankrupt by the curator in the decision number: 2/Pdt.Sus-Another-Lawsuit/2019/PN.Niaga jo. Verdict Number: 7/Pdt.Sus-PKPU/2018/PN. Niaga Mdn is not the asset of the bankrupt debtor. To determine the status of third party callateral objects in bankruptcy, it refers to the provisions of Article 21 of Law Number 37 of 2004. The phrase in this law is associated with Article 1131 of the Civil Code means all the debtor’s property, both movable and immovable, both existing and new in the future. The decision of the Panel of Judges in deciding this case, has provided legal protection to third parties as holders of fiduciary guarantees in bankruptcy in a preventive manner, namely the curator in carrying out his duties must apply the precautionary principle before determining the existence of assets by taking nto account the basis of the rights used as olleteral so that it can provide legal certainty. Meanwhile, repressively, by filing another lawsuit against the curator’s actions that include fiduciary guarantees in the bankruptcy filing.